The Style of Customer Decision Making in the Bugis Community in Jambi - Karim, Kurniati; Hosen, Ahmad (Faculty of Economics and Business, Hasanuddin University, 2020)
The Bugis tribe is one of the tribes that resides in South Sulawesi Province. This tribe is known to be very rational in acting and is always based on the teachings of the ancestors in the form of